Growth, yield and boron uptake by soybean under variable boron application in a Vertisol - H.K. Rai; Monika Singh; A.K. Shukla (Annals of Agricultural Research, 2022)
A field study was conducted at JNKVV research farm during kharif season of 2014-15 to evaluate the effect of boron application at different levels (0, 0.5, 1.0, 1.5 and 2.0 kg B ha–1) on growth attributes, yield and boron content in soybean. The results revealed that significantly higher plant height, boron content and uptake was found with the application of 2.0 kg B ha–1 as compared to control (no boron application). However, maximum dry biomass accumulation (5683.3 kg ha–1) and yield of seed (2769.0 kg ha–1) and stover (2911.8 kg ha–1) were found under application of 1.5 kg B ha–1. The application of 1.5 kg B ha–1 significantly increased the yield and boron content in soybean and buildup of available boron in soil over control and 0.5 kg B ha–1 treatment but statistically at par with 2.0 kg B ha–1 treatment and found suitable for soybean in a Vertisol.